Size-controlled nitrogen-containing mesoporous carbon nanospheres by one-step aqueous self-assembly strategy - Wang, Jia; Liu, Hongyang; Diao, Jiangyong; Gu, Xianmo; Wang, Haihua; Rong, Junfeng; Zong, Baoning; Su, Dang Sheng (Journal of materials chemistry. A, Materials for energy and sustainability, 2015)
Nitrogen-containing mesoporous carbon nanospheres with tunable sizes have been prepared through an aqueous self-assembly process with F127 as a template and morphological control agent, and 3-aminophenol as carbon and nitrogen sources. The sphere sizes could be simply tuned by optimizing the concentration of F127 and ammonia. Compared with a traditional nanocasting method and a hydrothermal process, the present one-step method has the striking features of a simple synthesis process and easy introduction of the nitrogen atom into the carbon nanospheres. The feasibility of the fabrication method may open up a new way for the synthesis of heteroatom-containing carbon nanospheres with mesoporous structure. The prepared nitrogen-containing mesoporous carbon nanospheres exhibit good catalytic performance in the direct dehydrogenation of ethylbenzene due to their unique mesostructure and abundant oxygen and nitrogen functional groups.